Efficiency Tests in Foreign Exchange Market - Yi Hsien Lee; Khatanbaatar Sodoikhuu (International Journal of Economics and Financial Issues, 2012)
The main purpose of the paper is applying filter rules to examine the efficiency of foreign exchange. This paper uses three strategies of filter rules (buy long, sell short, buy long and sell short strategies) to test the performance of the transaction for EUR, JPY, GBP. The findings show that people will obtain more return by taking buy long/ sell short strategies of filter rules without considering transaction cost. However, the transaction of these three foreign exchange rate (EUR, JPY, GBP) will be more efficient by considering transaction cost. The results imply the foreign exchange market is efficient for the EUR, JPY and GBP.